NIN-like protein 8 is a master regulator of nitrate-promoted seed germination in Arabidopsis - 矢野 亮一; Yan Dawei; Easwaran Vanathy; Chau Vivian; Okamoto Masanori; Ierullo Matthew; Kimura Mitsuhiro; Endo Akira; Yano Ryoichi; Pasha Asher; Gong Yunchen; Bi Yong-Mei; et al. (Nature Communications, 2016)
Seeds respond to multiple different environmental stimuli that regulate germination. Nitrate stimulates germination in many plants but how it does so remains unclear. Here we show that the Arabidopsis NIN-like protein 8 (NLP8) is essential for nitrate-promoted seed germination. Seed germination in nlp8 loss-of-function mutants does not respond to nitrate. NLP8 functions even in a nitrate reductase-deficient mutant background, and the requirement for NLP8 is conserved among Arabidopsis accessions. NLP8 reduces abscisic acid levels in a nitrate-dependent manner and directly binds to the promoter of CYP707A2, encoding an abscisic acid catabolic enzyme. Genetic analysis shows that NLP8-mediated promotion of seed germination by nitrate requires CYP707A2. Finally, we show that NLP8 localizes to nuclei and unlike NLP7, does not appear to be activated by nitrate-dependent nuclear retention of NLP7, suggesting that seeds have a unique mechanism for nitrate signalling.